She's so vain? A Q study of selfies and the curation of an online self. (June 2021) - Lazard, Lisa; Capdevila, Rose
Selfie posting is now a well-established practice, particularly for young women. However, it is nevertheless much maligned in popular discourses. As a counterpoint to digital narcissism, selfie posting is also constituted as relational. This Q methodological study explored how young women make sense of selfie practices. Twenty-seven young women aged 18–23 sorted a set of statements about selfies into a quasi-normal grid. These sorts were factor analysed to identify shared patterns. Four factors were identified which were subsequently analysed qualitatively, producing a narrative for each. These included (1) 'Presenting . . . Me!', (2) 'I am what I am', (3) 'Sharing is caring' and (4) 'The In-crowd – beautiful and popular'. The complexity of identity curation evidenced in this study highlights the importance of moving beyond both polarised characterisations and the pathologisation of young women selfie takers in order to explicate the interplay between normative femininities and the digital self.